Perancangan Sistem Pemantauan Lokal dan Jarak Jauh bagi Panel Surya - Wahmisari Priharti; Sony Sumaryo; Desri Kristina Silalahi; Yendi Surya Agung (Jurnal Rekayasa Elektrika, 2020)
Solar photovoltaic monitoring system can be directly conducted locally for the experimental purposes. However, indirect or remote monitoring is also needed since the solar panel are often installed in a a high place, rural location, or remote area. This study offers a dual solar panel monitoring system i.e. local and remote. Local monitoring system consists of voltage, current, temperature and light intensity sensors that were integrated in a kit called PVmeter. The data in the local monitoring system were displayed on a LCD or on a PC monitor using data logger. While in the remote monitoring system, the data were uploaded to the internet and displayed on Thinkspeak website hence the data are accessible whenever and wherever needed. In the local system, monitored data were successfully displayed on *.txt file format for every 5 minutes. While in the remote system, the data were successfully displayed on Thinkspeak website with a mean transfer rate of 52.5 seconds.